Identifying the Ingroup: A Closer Look at the Influence of Demographic Dissimilarity on Employee Social Identity - Chattopadhyay, Prithviraj; Tluchowska, Malgorzata; George, Elizabeth (Academy of Management Review, 2004)
Relational demography researchers have constructed models based on social identity theory and self-categorization theory, without fully incorporating their theoretical and empirical richness. We rectify this omission by constructing a model that includes key concepts from these theories and that predicts whether employees will identify with a particular demographic category or with their workgroup, or both. Propositions derived examine whether demographic dissimilarity will positively or negatively influence employee social identity.